2003
DOI: 10.1038/ng1267
|View full text |Cite
|
Sign up to set email alerts
|

An intronic SNP in a RUNX1 binding site of SLC22A4, encoding an organic cation transporter, is associated with rheumatoid arthritis

Abstract: Rheumatoid arthritis is a common inflammatory disease with complex genetic components. We investigated the genetic contribution of the cytokine gene cluster in chromosome 5q31 to susceptibility to rheumatoid arthritis in the Japanese population by case-control linkage disequilibrium (LD) mapping using single nucleotide polymorphisms (SNPs). Here we report that there is significant association between rheumatoid arthritis and the organic cation transporter gene SLC22A4 (P = 0.000034). We show that expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
454
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(475 citation statements)
references
References 41 publications
16
454
2
3
Order By: Relevance
“…Obvious candidates in the 19 regions should be investigated first, such as PADI4 on chromosome 1, recently identified in the Japanese population (37), TNFR2 on chromosome 1 (38,39), and RANK on chromosome 18 (8). The Japanese investigators have also recently reported a new RA "susceptibility" gene, SLC22A4 (organic cation transporter) on 5q31 (40), located 20 cM 5Ј to our chromosome 5 suggested locus. This might reflect the limited power of linkage studies compared with association analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Obvious candidates in the 19 regions should be investigated first, such as PADI4 on chromosome 1, recently identified in the Japanese population (37), TNFR2 on chromosome 1 (38,39), and RANK on chromosome 18 (8). The Japanese investigators have also recently reported a new RA "susceptibility" gene, SLC22A4 (organic cation transporter) on 5q31 (40), located 20 cM 5Ј to our chromosome 5 suggested locus. This might reflect the limited power of linkage studies compared with association analyses.…”
Section: Discussionmentioning
confidence: 99%
“…1). Identifying non-HLA susceptibility genes remains a challenge, but it was recently reported that a novel RA susceptibility gene, solute carrier 22 member 4 (SLC22A4; OMIM*604190), mapping to chromosome 5q31, had been identified in a Japanese population (2). The 5q31 region was targeted for investigation because it had previously shown linkage in family studies of Crohn's disease (CD), atopic dermatitis, and bronchial asthma, and the region harbors a cytokine gene cluster.…”
mentioning
confidence: 99%
“…In the Japanese study, single-marker and haplotype analysis showed convincing association with a singlenucleotide polymorphism (SNP) mapping to intron 2 of the SLC22A4 gene, but the SNP was not thought to play a functional role (2). Studies of an intron 1 SNP in linkage disequilibrium (LD) with it showed that the polymorphism affected binding of a transcription regulator, RUNX-1.…”
mentioning
confidence: 99%
“…12,13 Moreover, SNPs within SLC22A4 were also suggested to be associated with rheumatoid arthritis. 14 At the project's initiation, we selected a total of nineteen genes in the 5q31-33 region to test association with GD, all of which show a strong potential involvement in autoimmune and/or inflammatory diseases. Six known genes located in the region, D5S434-D5S436, were selected, namely LARS, POU4F3, TCERG1, PPP2R2B, DPYSL3 and SPINK1.…”
Section: Introductionmentioning
confidence: 99%
“…SLC22A4 and SLC22A5 had been reported to be associated with Crohn disease and rheumatoid arthritis, which, similar to GD, had the pathogenesis associated with inflammation and autoimmunity. [12][13][14] Given that these genes were chosen within a region with evidence for linkage to GD, and on the basis of our current understanding of GD etiopathology, they should be both positional and functional candidates.…”
Section: Introductionmentioning
confidence: 99%